2018
DOI: 10.13189/ujer.2018.060308
|View full text |Cite
|
Sign up to set email alerts
|

Science and Technology Course in Educational Information Network a Review on Videos

Abstract: The FATIH project is a project put in place by a protocol signed between the Ministry of National Education and the Ministry of Transport in order to obtain the highest level of efficiency and equal opportunities in education and training activities. Today, remote education applications have become compulsory in order to reach the rapidly changing and developing information network more easily and effectively. For this reason, an increase in distance education program designs has been observed in order to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The notable difference is that teachers, who prefer to use technology at a rate of 95% (frequently-occasionally) in teaching social studies, prefer to use EIN at only a rate of 60% (frequently -occasionally) in teaching social studies. Similar studies have shown that teachers do not have enough knowledge on EIN and that their frequency of EIN use is not sufficient [42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…The notable difference is that teachers, who prefer to use technology at a rate of 95% (frequently-occasionally) in teaching social studies, prefer to use EIN at only a rate of 60% (frequently -occasionally) in teaching social studies. Similar studies have shown that teachers do not have enough knowledge on EIN and that their frequency of EIN use is not sufficient [42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…The interactive application introduced by this researcher integrated the teaching of phonetic systems through a multisensory approach and managed to highlight visual, audio and kinaesthetic modalities in learning. This multisensory approach is used so that students can learn actively to help them perform effectively [41]. The results from the analysis of student score profiles based on the conducted pre-test and post-test using written test instruments and oral test instruments have shown that there was a positive increase in the percentage among the intermediate and high profile levels of students in the oral test instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the optimization algorithm, the metaheuristic algorithm is an improvement of the heuristic algorithm [8,9]. It combines two types of random algorithms and local search algorithms and, aiming at a specific problem, iteratively obtains an approximate optimal solution that can be used to calculate a given problem under the complexity of time and the complexity of a given area [10]. The overview diagram of the metaheuristic algorithm is shown in Figure 1.…”
Section: Design and Development Methods Ofmentioning
confidence: 99%